2021
DOI: 10.1002/acr.24232
|View full text |Cite
|
Sign up to set email alerts
|

Association of Quadriceps Adiposity With an Increase in Knee Cartilage, Meniscus, or Bone Marrow Lesions Over Three Years

Abstract: Objective. To evaluate the association of fatty infiltration of the quadriceps and vastus medialis (VM) with an increase in knee cartilage, meniscus, or bone marrow lesions, using magnetic resonance imaging (MRI) in knee osteoarthritis (OA) over 3 years.Methods. Participants (n = 69) with and without radiographic knee OA underwent MRI at baseline and 3 years later. Chemical shift-based water/fat MRI was used to quantify the intramuscular fat fraction and the lean anatomical cross-sectional area (ACSA) for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 22 publications
2
12
0
Order By: Relevance
“…One study using chemical shift-based water/fat MRI, found that the intramuscular fat fraction in the quadriceps and vastus medialis muscles was associated with increase of cartilage, meniscus, or BML scores on MRI over 3 years. The lean anatomical cross-sectional area of those muscles was not significantly associated with knee OA progression 45 . Consistent with the previous study, another study using ultrasound found that rectus femoris and vastus lateralis muscle echogenicity, representing fat content and fibrosis, was associated with mobility performance in women with knee OA, while, muscle thickness and subcutaneous fat thickness were not 46 .…”
Section: Imaging Of Peri-articular Tissues In Oamentioning
confidence: 87%
“…One study using chemical shift-based water/fat MRI, found that the intramuscular fat fraction in the quadriceps and vastus medialis muscles was associated with increase of cartilage, meniscus, or BML scores on MRI over 3 years. The lean anatomical cross-sectional area of those muscles was not significantly associated with knee OA progression 45 . Consistent with the previous study, another study using ultrasound found that rectus femoris and vastus lateralis muscle echogenicity, representing fat content and fibrosis, was associated with mobility performance in women with knee OA, while, muscle thickness and subcutaneous fat thickness were not 46 .…”
Section: Imaging Of Peri-articular Tissues In Oamentioning
confidence: 87%
“…Another study [6] indicated that an increase in VM fat content was related to cartilage loss but not to worsening knee symptoms. Further, a recent study [7] also suggested that the greater quadriceps fatty in ltration, speci cally in the VM, was associated with cartilage loss. All these ndings indicate towards a possible association of the VM muscle degeneration and progression of knee OA.…”
Section: Introductionmentioning
confidence: 95%
“…Few previous studies [5][6][7] have indicated that the vastus medialis (VM) muscle degeneration is associated with future cartilage loss. Wang et al [5] showed that the cross-sectional area (CSA) of the VM was negatively associated with cartilage volume loss and worsening symptoms over a period of two years.…”
Section: Introductionmentioning
confidence: 99%
“…The modern Dixon technique uses water/fat separation magnetic resonance imaging (MRI) based on chemical shift, which quantifies intramuscular adipose tissue and shows good consistency with magnetic resonance spectroscopy (MRS) ( 12 ). However, MRI not only visualizes the anatomical structure but also quantifies the proton density fat fraction (PDFF) with good spatial resolution, short acquisition time, and accurate fat quantification ( 13 , 14 ).…”
Section: Introductionmentioning
confidence: 99%